2020
DOI: 10.1021/acs.jafc.9b07965
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Induction Is a Rational Strategy to Enhance the Productivity of Antrodia cinnamomea Fermentations for the Antioxidant Secondary Metabolite Antrodin C

Abstract: Antioxidant metabolites contribute to alleviating oxidative stress caused by reactive oxygen species (ROS) in microorganisms. We utilized oxidative stressors such as hydrogen peroxide supplementation to increase the yield of the bioactive secondary metabolite antioxidant antrodin C in submerged fermentations of the medicinal mushroom Antrodia cinnamomea. Changes in the superoxide dismutase and catalase activities of the cells indicate that ROS are critical to promote antrodin C biosynthesis, while the ROS prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 55 publications
0
13
0
1
Order By: Relevance
“…2a, with 90 mM Vc supplementation at 4th day of fermentation, the activity of T-AOC of the cultures grown (6 d, 8 d, and 10 d) increased as the culture time went and reached its maximum at 10 d, and the T-AOC values at 6 d fermentation were signi cantly higher compared to the non-supplemented group (P < 0.05), indicating that Vc can greatly improve the antioxidant capacity as intended. In addition, as the rst line of defense, intracellular antioxidant enzymes, such as SOD and CAT, can protect cells from ROS damage [28]. It is generally believed that SOD and CAT have a synergistic effect on the oxidative protection in cells [23].…”
Section: Resultsmentioning
confidence: 99%
“…2a, with 90 mM Vc supplementation at 4th day of fermentation, the activity of T-AOC of the cultures grown (6 d, 8 d, and 10 d) increased as the culture time went and reached its maximum at 10 d, and the T-AOC values at 6 d fermentation were signi cantly higher compared to the non-supplemented group (P < 0.05), indicating that Vc can greatly improve the antioxidant capacity as intended. In addition, as the rst line of defense, intracellular antioxidant enzymes, such as SOD and CAT, can protect cells from ROS damage [28]. It is generally believed that SOD and CAT have a synergistic effect on the oxidative protection in cells [23].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, Clemons et al 55 have shown that two sizeindependent metrics namely, stereochemical complexity and shape complexity, are excellent predictors of target protein binding specicity of small molecules. Stereochemical complexity measures the ratio of the number of chiral carbon atoms to the total number of carbon atoms in a molecule, whereas shape complexity is the ratio of the number of sp 3 hybridized carbon atoms to the total number of sp 2 and sp 3 hybridized carbon atoms in a molecule. 55 Specically, Clemons et al 55 have correlated the stereochemical and shape complexity of small molecules with their target protein binding specicity across three representative small molecule collections namely, CC, DC 0 and NP (Methods).…”
Section: Physicochemical Properties Of Secondary Metabolites In Mefsamentioning
confidence: 99%
“… 1,2 Investigation of the fungal habitats has shed important insights into the stimulation and the biosynthesis of valuable secondary metabolites produced by fungi. 3 As a rich source of secondary metabolites, fungi are valuable contributors to the chemical diversity of the natural product space. Importantly, the fungal secondary metabolome is enriched in bioactive molecules and has immense potential for drug discovery 4 including antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Antrodia cinnamomea is a folk mushroom growing on the inner cavity of Cinnamomum kanehirae Hay, a member of the Lauraceae family only found in Taiwan [1][2][3][4]. Naturally, it is grown in the mountain ranges of Miaoli, Kaohsiung, Taitung and Taoyuan [5], and it is commonly known by its Chinese name as "Niu-chang chih" [1].…”
Section: Introductionmentioning
confidence: 99%